Ansiedad y su incidencia en el autoconcepto en una joven de 23 años del cantón Montalvo - López Bajaña, Carmen Belén (2022)
The present case study aims to identify the main factors and causes of anxiety problems in the 23-year-old girl and how they affect her emotional state, through applied techniques such as direct observation, unstructured interviews for data collection for the psychological medical history and finally applying the Hamilton test to check the level of anxiety in the patient. A therapeutic plan is provided which consists of 4 techniques and 4 activities in a total of 7 sessions, the same that are selected from cognitive behavioral therapy to modify automatic thoughts that generate stressful situations in the patient, which presented collaboration and acceptance to the changes that occur, the various authors and different sources of information were very important to investigate the main factors that alter the levels of anxiety.